Adapting and monitoring daily CICO implementation in high schools. Issue 1 (3rd January 2023) - Kato, Mimi McGrath; Kittelman, Angus; Flannery, K. Brigid; Cohen Lissman, Dana
Abstract: Previous research has demonstrated a need for contextual fit when implementing behavior supports in high schools (Flannery et al., The High School Journal, 96 (4), 267–282, 2013; Flannery & Kato, Preventing School Failure: Alternative Education for Children and Youth, 61 (1), 69–79, 2017). As high schools move beyond the implementation of Tier 1 and begin to implement Tiers 2 and 3, school implementation teams must identify effective interventions that fit the high school context. The current study assessed whether Check-In Check-Out (CICO; Hawken et al., Responding to problem behavior in schools: The check-in, check-out intervention (3rd ed.). The Guilford Press, 2021), with strategic contextual adaptations, could be implemented with fidelity and whether high daily implementation fidelity was related to student behavior performance. Teacher feedback quality was also explored. Results showed high fidelity implementation at the systems and procedural level for all participants and a significant, small correlation between procedural fidelity and daily points earned.